Abordagem computacional no desenvolvimento de padrões de crochê - André Luiz Silva (2021)
The creative potential found in computational structures offers possibilities to exploration in the fields of Art, Design, Architecture and Music. Through the context of artisanal production, these potentialities generate forces of innovation and the emergence of previously unexplored results. However, along with this trend, questions also arise about technical feasibility, sustainability, autonomy, complexity, aesthetics and poetics. That said, this dissertation is a theoretical-practical research in which these questions were approached from an experiment involving an algorithm with creative autonomy and the crochêt technique. The experiment considers the presence of both the artisan and the designer. It was produced through artistic and exploration potential where computational creativity could offer to the artisanal production system. The questions about sustainability, autonomy and technical feasibility could be understood through the understanding of this structure formed by the craftsman, computer and designer as a complex system, without hierarchy and with collaboration. From this work structure emerged results with poetic and artistic potential, representing an alternative for the interaction of our traditional knowledge with computational technologies.